Круглый стол "Реструктурация личности в нестабильном обществе: изменение жизненных миров, разрушение идентичностей, маргинализация" - Шульга, Н.; Макеев, С.; Злобина, Е.; Бевзенко, Л.; Рудницкая, Т.; Ануфриева, Р.; Мартынюк, И.; Соболева, Н.; Резник, А.; Ходоровская, Н.; Сохань, Л.; Бойко, Н. (Социология: теория, методы, маркетинг, 2000)
On June 16, 2000, Institute of Sociology of the NAS of Ukraine organized and conducted round table “The Restructuration of Personality in Unstable Society: Changing of Living Worlds, Destruction of Identities, Marginalisation” where leading Ukrainian sociologists discussed current situation and trends of Ukrainian society concerning the problem of changing the personal social practics, particularly, the question of marginalisation in unstable social conditions.